Management model of tourism village based green tourism through a holistic approach in Blimbingsari Tourism Village, Melaya District Jembrana Regency - I Nyoman Meirejeki; I Ketut Suarta; I Komang Mahayana Putra; Anak Agung Putu Swabawa; Putu Dana Pariawan Salain (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study aims to design a tourism village management model in empowering the potential of tourism attractions and communities based on green tourism in Blimbingsari Village by using a holistic approach effectively. Data collection using survey methods, interviews, and Focus Group Discussion with judgment sampling method. Data analysis used descriptive methods based on input from selected people such as village heads, hamlet heads, youth association leader, tourism awareness groups and tourism actors in Blimbingsari village. Based on the results of the analysis, it shows a tourism village management model based on green tourism with a holistic approach seen from two aspects. In general, the management model related to the management of personal and communal tourism products goes through two stages, namely: 1) determining the unit according to operational demands, 2) making fair policies and rules in creating stability in operations. From the component aspect, management is carried out by involving all stakeholders who contribute to the development of the Blimbingsari tourism village, namely: government, private sector, community and managers. A holistic approach is applied when making fair policies that can meet the interests of the village and tourism product providers in Blimbingsari village. Its application also involves all stakeholders, because it can help develop a comprehensive tourism village that can create an integrated tourism village. So that the tourism village management model through a holistic approach will be able to create harmony in the community and be able to maintain environmental sustainability in the context of green tourism.